Soil Texture Distribution in Al-Muthanna Governorate and Its Relationship with Morphological Characteristics Using GIS Techniques (The International Journal for Scientific Research, 2025)
The study was conducted on the soils of Al-Muthanna Governorate, southern Iraq, to determine their physical and morphological characteristics. The results revealed significant variations in sand and clay proportions among the sites: clay-dominated soils in Al-Najmi (430 g/kg clay), sandy soils in Al-Rumaitha (860 g/kg sand), and relatively balanced textures in Al-Samawa (240 g/kg clay, 220 g/kg sand). Distinct color differences were also observed, such as dark brown (10YR3/2) in Al-Najmi and light gray (10YR7/2) in Al-Khidhir, reflecting variations in moisture and mineral content. Geographic Information System (GIS) analysis showed that the northern part of the governorate is rich in clay and silt due to fluvial deposition, while the southern areas (Bsiya and the desert) are dominated by sandy soils as a result of aridity. These variations are crucial for crop selection; sandy soils are characterized by good drainage, whereas clayey soils retain water. The study highlights the importance of applying GIS and remote sensing techniques for sustainable soil management strategies.
Keywords: Soil Texture; Geographic Information System (GIS); Physical Properties; Morphological Properties; Munsell Color Atlas